Numerical modelling of castings - Mazánková, Martina J.; Hloušek, Jiřί (Computer Assisted Methods in Engineering and Science, 2023)
The presented work shows one of possibilities of numerical modelling of castings. The simulation is a base of modern design. The finite difference simulation program enables computer aided calculations of a form filling and solidification. It is possible to analyse thermal behaviour of the casting, cooling, or heating system with the simulation. The optimisation of the process can be handled easily by a user of the software.